Comparison of cardiac output measurements using transpulmonary thermodilution and conventional thermodilution techniques in anaesthetized dogs with fluid overload. (15th December 2015) - Itami, Takaharu; Endo, Yusuke; Hanazono, Kiwamu; Ishizuka, Tomohito; Tamura, Jun; Miyoshi, Kenjiro; Sano, Tadashi; Yamashita, Kazuto
Abstract: Objective: To evaluate the agreement between cardiac output (CO) values obtained using a transpulmonary thermodilution technique (TPTDCO) and conventional thermodilution technique (TDCO) in anaesthetized dogs with fluid overload. Study design: Prospective experimental study. Animals: Six healthy Beagle dogs aged 7–8 years. Methods: Dogs were anaesthetized with sevoflurane in oxygen, and catheters were inserted for TPTDCO and TDCO measurement. After instrumentation, baseline CO was measured using each technique at a central venous pressure (CVP) of 3–7 mmHg. Dogs were subsequently administered lactated Ringer's solution and 6% hydroxyethyl starch to induce fluid overload. CO measurements were obtained using each technique at CVP values of 8–12 mmHg, 13–17 mmHg, 18–22 mmHg and 23–27 mmHg. Agreements between CO measurements obtained with the respective techniques were analysed using Dunnett's test, Pearson's correlation coefficient and Bland–Altman analysis. Results: Thirty pairs of CO values were obtained, ranging from 1.45 L minute −1 to 4.69 L minute −1 for TPTDCO and from 1.30 L minute −1 to 4.61 L minute −1 for TDCO. TPTDCO and TDCO values correlated strongly ( r 2 = 0.915, p < 0.001). The bias and mean relative bias between TPTDCO and TDCO were 0.26 ± 0.30 L minute −1 (limits of agreement − 0.29 to 0.81 L minute −1 ) and 9.7%, respectively. Conclusions and clinical relevance: TPTDCO and TDCO measurements obtained in anaesthetized dogs during fluid overload exhibited good agreement. Accordingly, transpulmonary thermodilution provides an accurate measurement of CO in dogs with fluid overload.